THE ANALYSIS OF PERSONALITY AND CONFLICTS OF HARRY POTTER NOVEL - Rifka Tsamrotul Fuadah; Ria Kamilah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2023)
The purpose of this study is to analyze the psychology of personality and conflict experienced by the main character. Researchers used library research methods. The results of Harry Potter's Personality Psychology research found that he was a brave, self-confident and not easily discouraged person. Apart from that, the conflicts that were found were Harry Potter being attacked by a giant dog in the corridor on the third floor, the main character finding a deadly plant, the event where they fought to find flying keys, the event where there was a game of chess, and finally the event where the main character got lucky in the struggle. stone.